2012
DOI: 10.1128/iai.06069-11
|View full text |Cite
|
Sign up to set email alerts
|

Perinuclear Localization of Internalized Outer Membrane Vesicles Carrying Active Cytolethal Distending Toxin from Aggregatibacter actinomycetemcomitans

Abstract: Aggregatibacter actinomycetemcomitans is implicated in aggressive forms of periodontitis. Similarly to several other Gramnegative species, this organism produces and excretes a cytolethal distending toxin (CDT), a genotoxin associated with cell distention, G 2 cell cycle arrest, and/or apoptosis in many mammalian cell types. In this study, we have identified A. actinomycetemcomitans outer membrane vesicles (OMVs) as a vehicle for simultaneous delivery of multiple proteins, including CDT, into human cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(152 citation statements)
references
References 71 publications
(87 reference statements)
3
146
0
Order By: Relevance
“…A possible explanation for such observations may be that endocytic pathways differ based on the size of the particle (65,66). Thus, as A. actinomycetemcomitans, similar to many additional bacterial species, disseminates vesicles of heterogenous sizes (approximately 10 to 300 nm in diameter) (3,7,19,48), differentially sized subpopulations of bacterial OMVs may be internalized via discrete pathways of endocytosis. A. actinomycetemcomitans OMV uptake was only partly reduced by filipin III, an inhibitor of caveola-dependent endocytosis (62,67,68), preventing OMV colocalization with caveolin protein (69).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible explanation for such observations may be that endocytic pathways differ based on the size of the particle (65,66). Thus, as A. actinomycetemcomitans, similar to many additional bacterial species, disseminates vesicles of heterogenous sizes (approximately 10 to 300 nm in diameter) (3,7,19,48), differentially sized subpopulations of bacterial OMVs may be internalized via discrete pathways of endocytosis. A. actinomycetemcomitans OMV uptake was only partly reduced by filipin III, an inhibitor of caveola-dependent endocytosis (62,67,68), preventing OMV colocalization with caveolin protein (69).…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) released by this organism carry multiple proteins, and density gradient centrifugation supports the notion that there may be subpopulations of vesicles exhibiting slight variations in protein composition (7,19). Further to earlier reports revealing the OMV association of leukotoxin (LtxA) and a concomitant leukotoxic activity of A. actinomycetemcomitans OMVs (19,20), we have demonstrated that the OMVs could simultaneously deliver multiple proteins, including OmpA and biologically active cytolethal distending toxin (CDT), into HeLa cells and human gingival fibroblasts (HGF) (7). Hence, OMVs released by this species likely play a role in periodontal disease by delivering biologically active toxins and additional virulence factors into susceptible cells of the periodontium.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…These observations reinforced the intuitive prediction that OMVs likely form at regions of the OM that are only loosely connected to PG, an idea that remains an important consideration in developing models for OMV biogenesis. Integral OM transporters and porins are commonly identified in OMVs [Lee et al, 2008], including members of the OmpA family [Berlanda Scorza et al, 2008;Kesty et al, 2004;McMahon et al, 2012;Rompikuntal et al, 2012;Sidhu et al, 2008], which are interesting because they can function both as porins or as lipoprotein-like tethers between the OM and PG, depending upon their conformation [Nikaido, 2003]. OMVs have also been shown to contain many proteins of periplasmic origin, giving rise to the idea that OMV formation can serve as a secretory or excretory mechanism for select proteins [Chatterjee and Das, 1967;Kadurugamuwa and Beveridge, 1995].…”
Section: Proteins Associated With Omvsmentioning
confidence: 99%